Globalisasi, Persaingan Bebas, dan Ekonomika Etika - Hamid, Edy Suandi (Unisia, 2016)
The following article investigates the realities of economic life that those are not in^ accordance with the basic norms of society, those of local and international. These realities happen because economics deviated from basic philosophy to give welfare for human life. The doctrine of economics that teaches personal interest produces human as homo economicus. This doctrine causes human free from his/her nature as homo socius. In this sense according to the writer ofarticle below for the future it will need the deliberated movement to develop the science of economic toward more humanistic or more ethic.